Activities Carried Out By The Minister of National Education Mustafa Necati Bey to Teach The New Turkish Alphabet - Fahri Kılıç (Yakın Dönem Türkiye Araştırmaları)
Mustafa Necati Bey (1892–1929), played an active role in the organization of West Anatolia National Forces through his writings in various journals and newspapers during the National Struggle Period. Being a member of the Grand National Assembly of Turkey (GNAT) for Saruhan (Manisa) and İzmir after its formation, Mustafa Necati Bey also subsequently served as the head of the Independence Courts, minister of population exchange, development and housing, minister of justice, and minister of education. Especially during his ministry of education, he was well known for his comprehensive works for organizing national education, preparing the new Turkish alphabet, and founding the public schools. This research addresses the activities carried out by theMinister of Education, Mustafa Necati Bey, to teach the new Turkish alphabet to the public, and it is based on archival sources of the period as well as periodicals, surveys, articles, theses, and memoirs.